Membentuk Identitas Muslimah Modern: Strategi Pemasaran Digital UMK Hijab di Makassar - Syam, Syachriani; Utami, Dian Gita Utami (Jurnal Paradigma, 2026)
BIAH hijab is a small local business in the fashion industry that produces various types of hijabs, collaborates with local tailors, and utilizes digital platforms as its primary marketing medium. Despite these efforts, the brand faces low awareness, resulting in many potential customers being unfamiliar with BIAH Hijab and a number of transactions being canceled. In the current digital era, people increasingly obtain information through the internet, creating opportunities for digital marketing to address these issues. This study aims to assist BIAH Hijab in overcoming promotional challenges and improving brand visibility. The research employs a descriptive qualitative method. Data were collected through observation, interviews, and documentation, and analyzed descriptively using a SWOT framework to assess strengths, weaknesses, opportunities, and threats. The analysis reveals that BIAH Hijab has strong product quality and local partnerships but faces weaknesses in promotional consistency. Opportunities exist in expanding digital marketing channels and influencer collaborations, while threats include intense market competition. The study recommends that BIAH Hijab develop a structured digital marketing strategy, strengthen collaborations with external partners, and leverage data analytics to enhance campaign performance. Keyword: Digital Marketing, BIAH hijab, SWOT, Social Media, Muslimah Fashion